The Ruling on Having Intercourse with a Wife who has Completed Her Menses but has not done the Obligatory Ghusl according to Imam Abu Hanifah - Ramadhan, Alif Randi; Pasaribu, Ilhamsyah (Law Development Journal, 2023)
The purpose of this study aims to analyze the opinion of imam Abu Hanifah regarding the opinion of having sex with a wife who has finished her period but has not taken the obligatory bath. The type of research used is library research, with qualitative analysis methods using data in the form of verses of the Qur'an and hadith in various books of interpretation that contain related information. In this case, the author selects the data to be included in the writing according to the existing rules so that it can be easily understood regarding the sequence of the data to be analyzed using interpretation, through the data by using the rules of fiqh, while in analyzing the data collected through deductive and inductive methods, to implement the problem of menstruation when taking the opinion of imam Abu Hanifah based on the Qur'an and hadith. The conclusion of this research is the opinion of Imam Abu Hanifah that if the husband wants to have intercourse with his wife who has finished menstruating but has not taken a bath, it is permissible to have sexual intercourse even though he has not had time to take a janabah bath. The most important thing is that the blood has really stopped and does not come out again according to the conditions that have been determined. This research is expected to contribute to increasing understanding of the importance of understanding the relationship between wife and husband in the household. The findings of this study can be a reference for related parties, including family members, communities and educational institutions in realizing a good family.